Structure, Process, and Outcome Evaluation of Hospitals about Neonatal Screening Program in Karbala in 2022 (Journal of Pharmaceutical Negative Results, 2022)
Background: The newborn screening program has been evaluated in several parts of the world, with varying outcomes (1). In terms of incidence, severity, age of onset, and diagnostic and therapeutic techniques, they vary greatly. The program screens a group of conditions that causes major metabolic abnormalities in newborns, resulting in irreversible damage and illness. There is a treatment for some of them that, if given soon after birth, can prevent such damage. Many countries have suggested, developed, and implemented population-based newborn screening for these illnesses, although at differing rates and using various criteria(2). Materials and Methods: This evaluation study was conducted between the first of September 2021 and the end of June 2022. This research was carried out in the Holy Karbala Governorate, to assess a pilot program implemented by the Governorate Directorate of Health in Karbala Children's Teaching Hospital and Al-Hindiya General Hospital. A checklist has been used to evaluate hospitals after reviewing the “National Guideline of Newborn Screening for Care Providers in Primary Health Care Centers in Iraq”. The list was built and developed by the researchers. Results: It was documented that the program worked in only one hospital, where the trained medical staff. However, there was untrained health staff available, in addition to the lack of the program’s needs for laboratory testing follow-up, food, and milk needed for the program patients. Conclusion: Although, this program could contribute to “reducing the rate of under-five mortality by two-thirds”, the necessary tools to meet these objectives were not found in the hospitals.